Existence of Solutions to Elliptic Equations with Variable Exponents and a Singular Term (Communications in Mathematical Research, 2021)
The purpose of this paper is to study a class of elliptic equations withvariable exponents. By using the method of regularization and a priori estimates, weobtain the existence of weak solutions to these problems.